Validation of the Persian version of Skindex-16 among older patients with skin diseases - Tahereh Mahdavi nejad; Fatemeh Mohammadi; Ozkan Gorgulu; Seyedeh Ameneh Motalebi; Zahra Hosseinkhani (BMC Geriatrics, 2021)
Abstract Background Skin conditions often considerably impact the older patients’ psycho-social health and quality of life (QoL). The present study was aimed to examine the validity and reliability of the Persian version of Skindex-16 among older people with skin diseases. Methods In this validation study, 260 older patients suffering from a range of skin conditions were recruited from a dermatology clinic in Rasht, Iran. Data were collected using a checklist for demographic and clinical characteristics and the Skindex-16 questionnaire. In this study, validity (face, content, and construct) and reliability (Cronbach’s alpha) of the Skindex-16 were assessed and reported. Results The mean age of participants was 64.51 ± 5.04 years. The results of confirmatory factor analysis showed that the model had acceptable fitness into the expected three-factor structure [χ 2 /df = 249.363, P < 0.001; GFI = 0.961; TLI =0.952; RMSEA = 0.078 (90% CI = 0.06, 0.09) and SRMR = 0.06]. The reliability analysis results confirmed that the values of Cronbach’s alpha coefficient for Skindex-16 were in the acceptable range (0.923). Conclusions Our evaluation of the Skindex-16 indicates that it is reliable and a valid instrument that can be used for measuring QoL for Iranian dermatologic patients.